Combined treatment of acute maxillary sinusitis - A. I. Kryukov; A. B. Turovskiy; G. Y. Tsarapkin; G. N. Izotova; A. S. Tovmasyan; K. M. Fedotkina; D. S. Gorin (Медицинский совет, 2015)
Chronic rhinosinusitis is a relevant healthcare issue the incidence of which has increased twofold over the past 20 years. According to the literature, the incidence grows with age: in people aged 20 to 29 years, it equals 2.7%, and in people from 50 to 59 years - 6.6% [1]. Against a background of population ageing, inflammatory diseases of the paranasal sinuses (PNS) are becoming a challenge. Women suffer from chronic sinusitis 1.5 times more often than men. 15 to 36% of in-patients at ENT units are people suffering from diseases of the paranasal sinuses (PNS) [2].